UMPSA BJTU Dual Degree Programme pioneer graduates enhance nations rail industry development - Mimi Rabita, Abd Wahit (UMPSA, 2025)
BEIJING, 8 January 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) marked a new milestone when the first cohort of 45 graduates from the UMPSA-Beijing Jiaotong University (BJTU) collaboration programme completed their studies in Railway Engineering.